CARACTERIZAÇÃO, VALIDAÇÃO ANALÍTICA E ESTUDO DE TOXICIDADE DE NANOCÁPSULAS CONTENDO NARINGINA - BUDEL, Renata Gancine (2018)
Oxidative stress is a major factor in the development of neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease. Naringin is a flavonoid widely known for its pharmacological properties, among them anti-inflammatory and antioxidant, being an adjuvant to prevent neurological oxidative damage. Studies performed in vitro and/or in vivo indicate that naringin is able to reduce oxidative damage by preventing the formation of free radicals in neural tissue. Although naringin is an active easily found in citrus fruits, it has low bioavailability, biodistribution and also is biotransformed in naringenin, causing it to reach the nervous system in low concentrations, limiting the effects described. The use of nanocapsules as drugs carriers can increase solubility, improve biodistribution, prevent drug biotransformation, and thus may improve the performance of naringin in the treatment of neurological diseases. Therefore, the objective of this work is to produce a nanocapsules loaded with naringin, to evaluate its physicochemical characteristics, to quantifying the naringin by the analytical method using High Performance Liquid Chromatography (HPLC), evaluating its safety and its potential in vitro neuroprotective effect in vitro. For such, free nanocapsules (FN, without active) and containing naringin (NN) at the concentration of 2 mg / mL were prepared by interfacial deposition of the preformed polymer, followed by physicochemical characterization and quantification of naringin by HPLC. The toxicity of the formulations was evaluated in vitro whit rat hippocampal slices and in vivo using C. elegans and Danio rerio (zebrafish). The evaluation of neuroprotective effect against oxidative damage was performed in hippocampal slices in vitro. The procedures described were approved by the Ethics Committee on the Use of Animals (CEUA) of the Franciscan University (UFN, protocol 02/2017) and the Pontifical Catholic University of Rio Grande do Sul (PUCRS, 8080/2017). The formulations produced were homogeneous, of slightly bluish white color. The particle size was from about 94 nm to FN and 83 nm to NN. The zeta potential was -19.3 mV and -15 mV, for NB and NN, respectively. Both nanoparticles had a polydispersity index below 0.3, and pH ± 3.7. The analytical parameters linearity, specificity, precision, accuracy, limit of detection and quantification, and robustness indicated suitability of the analytical method for quantification of naringin by HPLC. There was no indication of toxicity by the nanocapsules in the analyzes assays. In hippocampal slices subjected to oxidative damage, naringin induced a partial protective effect of naringin-loaded nanocapsules was observed, however, with no difference in relation to the active in the free form. Thus, in the present work was possible to produce naringin-loaded nanocapsules successfully, validating an analytical method by HPLC that ensured the naringin quantification in nanocapsule suspensions, according to the requirements of the regulatory agencies. The nanocapsules did not demonstrate toxicity in C. elegans nor zebrafish by means of the evaluated parameters. The potential neuroprotective effect of nanocapsules with naringin should be further explored to confirm its use against damage to the central nervous system.